Development and application of the antigen microarray for the detection of autoantibodies in hepatocellular carcinoma patients - Afriyie-Asante, Afrakoma (2019)
Hepatocellular carcinoma (HCC) is a primary liver cancer characterised by mutations in the cellular machinery, which induces the liver cells to replicate at a higher rate. It is the fifth most common cancer and the third most common cause of cancer-related deaths worldwide. The extensive prevalence of this malignancy carries a significant economic burden on a country. HCC occurs within the background of cirrhosis and chronic liver diseases, where hepatitis B virus (HBV), hepatitis C virus (HCV) infections and alcoholism are regarded as the most frequent risk factors of the disease. However, current diagnostic tools are sensitive only at the advanced stages, which hugely contribute to the grave prognosis and compromised effective curative treatment, resulting in poor 5-year patient survival. With the continuous devastating effect of this malignancy, there is an urgent need for an efficient tool, which could detect the malignancy at both the early and late stages.